2015
DOI: 10.1080/10919392.2015.1033940
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Use of Social Media: Technology Affordance and External Stakeholder Relations

Abstract: A c c e p t e d M a n u s c r i p t 2 Dr. Kafui Monu is an assistant professor of computer information systems at Savannah State University. He holds a doctoral degree from the University of British Columbia. Professor Monu's main area of research is system analysis and design, with special interest in helping developers meet user expectations through conceptual modeling. His work includes representing users' decision-making processes to system designers. Dr. Kofu's earlier work focused on disaster management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…Social media affordance deals with those hidden possibilities that establish a link between the user and social media (Cabiddu, 2014). Prior research shows that scholars used affordance theory to define the role of social media in organizational practices, which includes knowledge sharing (Gibbs, Rozaidi, & Eisenberg, 2013;Majchrzak, 2013), knowledge creation (Mansour, 2013;Wagner, 2014), external communication (Argyris, 2015), intellectual capital production (Kane, 2011), election campaigns (Dyrby, 2012), activism (Obar, 2014), customer engagement (Cabiddu et al, 2014), and government openness (Malsbender, 2013;Stamati, 2015).…”
Section: Social Media Affordancementioning
confidence: 99%
“…Social media affordance deals with those hidden possibilities that establish a link between the user and social media (Cabiddu, 2014). Prior research shows that scholars used affordance theory to define the role of social media in organizational practices, which includes knowledge sharing (Gibbs, Rozaidi, & Eisenberg, 2013;Majchrzak, 2013), knowledge creation (Mansour, 2013;Wagner, 2014), external communication (Argyris, 2015), intellectual capital production (Kane, 2011), election campaigns (Dyrby, 2012), activism (Obar, 2014), customer engagement (Cabiddu et al, 2014), and government openness (Malsbender, 2013;Stamati, 2015).…”
Section: Social Media Affordancementioning
confidence: 99%
“…According to Treem and Leonardi (), this increased visibility has the potential to present information communally, which means contributions can be easily located and viewed by other coworkers, as well as even generate metaknowledge that is not available in any traditional knowledge repositories or elsewhere. In addition, posts, comments, status updates, votes, revisions, and other forms of information sharing frequently afford improved transparency of ongoing or planned organizational activities (Zhao & Rosson, ) and are therefore invaluable for the corporate setting (Argyris & Monu, ). Particularly in the health care industry, where collaboration and knowledge exchange are crucial for delivering high‐quality services (Cnossen, ; Merrick, Joanne, & Scott, ), PSN may unfold new opportunities in the discovery of expertise, facilitation of cross‐boundary collaboration, preservation of the institutional memory, and harness of distributed knowledge of health workers and patients (Miller, Marks, & DeCoulode, ).…”
Section: Introductionmentioning
confidence: 99%
“…Freeman's Stakeholder Theory [27] describes such stakeholders as anyone "who can affect or is affected by the achievement of the organisation's objectives" which includes customers, shareholders and suppliers. Argyris and Monu [28] argue that the primary function of EC is to build relationships with customers and to increase loyalty. Research [29] suggests that the utilisation of SM in support of EC speeds up communication and also improves its effectiveness and reach.…”
Section: External Communication and Smmentioning
confidence: 99%
“…In a survey based on 2,100 companies, Harvard Business Review [30] found that the most common SM tools used for EC included social networking sites, micro-blogging, wikis and video sharing. Argyris and Monu's [28] 'Eight Affordances' represent the competencies of SM tools which include: Presentability; Self-Expression; Monitorability; Reach; Engagement; Connectivity; Recordability; and Availability. These cover activities of SM with EC such as engaging with stakeholders, collecting data from stakeholders and facilitated monitoring of EC efforts.…”
Section: External Communication and Smmentioning
confidence: 99%